Supramolecular reassembly of self-exfoliated ionic covalent organic nanosheets for label-free detection of double-stranded DNA - Mal, Arindam; Mishra, Rakesh K.; Praveen, Vakayil K.; Khayum, M. Abdul; Banerjee, Rahul; Ajayaghosh, Ayyappanpillai (Angewandte Chemie-International Edition, 2018)
Ionic covalent organic nanosheets (iCONs), a member of the two-dimensional (2D) nanomaterials family, offer a unique functional platform for a wide range of applications. Herein, we explore the potential of an ethidium bromide (EB)-based covalent organic framework (EB-TFP) that self-exfoliates in water resulting in 2D ionic covalent organic nanosheets (EB-TFP-iCONs) for the selective detection of double-stranded DNA (dsDNA). In an aqueous medium, the self-exfoliated EB-TFP-iCONs reassemble in the presence of dsDNA resulting in hybrid EB-TFP-iCONs-DNA crystalline nanosheets with enhanced fluorescence at 600 nm. Detailed steady-state and time-resolved emission studies revealed that the reassembly phenomenon was highly selective for dsDNA when compared to single-stranded DNA (ssDNA), which allowed us to use the EB-TFP-iCONs as a 2D fluorescent platform for the label-free detection of complementary DNA strands.
Keywords: Covalent organic framework; DNA; ionic assembly; ionic covalent organic nanosheets; label-free detection